Generalized Wigner-Smith analysis of resonance perturbations in arbitrary Q non-Hermitian systems - Niall Byrnes; Matthew R. Foreman (Physical Review Research)
Perturbing resonant systems causes shifts in their associated scattering poles in the complex plane. In a previous study [N. Byrnes and M. R. Foreman, arXiv:2408.11360], we demonstrated that these shifts can be calculated numerically by analyzing the residue of a generalized Wigner-Smith operator associated with the perturbation parameter. In this work, we extend this approach by connecting the Wigner-Smith formalism with results from standard electromagnetic perturbation theory applicable to open systems with resonances of arbitrary quality factors. We further demonstrate the utility of the method through several numerical examples, including the inverse design of a multilayered nanoresonator sensor and an analysis of the enhanced sensitivity of scattering zeros to perturbations.